2010
DOI: 10.3174/ajnr.a2271
|View full text |Cite
|
Sign up to set email alerts
|

Final Cerebral Infarct Volume Is Predictable by MR Imaging at 1 Week

Abstract: BACKGROUND AND PURPOSE:Stroke volume, an increasingly used end point in phase II trials, is considered stationary at least 30 days after the ictus. We investigated whether information conveyed by MR imaging measurements of the "final" infarct volume could be assessed as early as the subacute stage (days 3-6), rather than waiting for the chronic stage (days 30 -45).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Several studies have shown that a FLAIR sequence performed at 3 to 5 days may be the most accurate early indicator of true infarct volume. 24 However, the timing of this imaging sequence may result in loss to follow-up as some patients may not be available to undergo the study because of either death or early discharge. In addition, at that point in time, the FLAIR sequence incorporates a certain element of edema that may result in overrepresentation of the final infarct lesion.…”
Section: December 2012mentioning
confidence: 99%
“…Several studies have shown that a FLAIR sequence performed at 3 to 5 days may be the most accurate early indicator of true infarct volume. 24 However, the timing of this imaging sequence may result in loss to follow-up as some patients may not be available to undergo the study because of either death or early discharge. In addition, at that point in time, the FLAIR sequence incorporates a certain element of edema that may result in overrepresentation of the final infarct lesion.…”
Section: December 2012mentioning
confidence: 99%
“…Postoperative metabolic and immunologic changes are proportional to the degree of surgical trauma and subsequent changes may be implicated in the development of septic complications and tumor metastasis formation [9,10,11,12]. There are currently various data showing that laparoscopy results in a reduction of the inflammatory response and preservation of the patients’ immune functions [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…7,13,14 In addition, infarct volume on FLAIR images is found to decrease over time within 1 month, but disappearance of infarcts on FLAIR has, to the best of our knowledge, never been reported. 15 These results suggest that the absence of a relationship between a high-risk plaque with IPH or TRFC components and the presence of infarcts on FLAIR images could not be explained by the rather long time interval between index event and imaging (median, 45 days; range, 7-100 days). Nevertheless, because FLAIR images also show infarcts older than the index event, this might explain why in the current study the presence of IPH and TRFC does not correlate with cerebral infarcts on MRI, in contrast to previously published studies on diffusion-weighted imaging positive infarcts in an early phase after the ischemic symptoms.…”
Section: Discussionmentioning
confidence: 69%